Energy efficient feedback-based scheduler for delay guarantees in IEEE 802.11e networks - G. Boggia; P. Camarda; L.A. Grieco; S. Mascolo (Computer Communications, 2006)
Energy saving algorithms for 802.11 Wireless LAN (WLAN) are basically based on keeping in a low-power state the Wireless Network Interface Card (WNIC) whenever a wireless station does not have frames to be transmitted/received. This can severely affect the QoS of the service provided to higher layers due to the transient time needed to switch from a low-power to a high-power state. Recently, the 802.11e Working Group (WG) has proposed a set of innovative functionalities in order to provide QoS in WLANs. In particular, the core of the 802.11e proposal is the Hybrid Coordination Function (HCF), which has a HCF Controlled Channel Access (HCCA) and an Enhanced Distributed Coordination Access (EDCA). In this paper, an innovative HCCA-based algorithm, which will be referred to as Power Save Feedback Based Dynamic Scheduler (PS FBDS), has been proposed to provide bounded delays while ensuring energy saving. Using ns-2 simulations, it has been shown that PS FBDS is able to provide a good trade-off between QoS and power saving at both low and high network loads.
Wirelsess Senson Networks and Wired/Wireless Internet Communications
Keywords: WLAN; Power saving; QoS; Dynamic bandwidth allocation; Feedback control